Perbedaan Fungsi Kognitif Mahasiswa Fakultas Kedokteran Unissula dengan IPK Kurang dari 3 dan IPK Lebih sama dengan 3 Yudisium Tahun 2018 - Ahmadi NH; Elly Noerhidajati; Siti Maesaroh (Proceedings of The ICECRS, 2019)
Cognitive function varies in each human being, from simple to complex, requiring attention, concentration, and coordination. Cognitive is related to a person's ability to think, solve problems, organize and also to communicate and interact with others and the environment. Methods: cross-sectional research, samples involve the students of medical faculty of Unissula-Semarang with GPA less than 3 and more than 3 graduated in 2018, instrument Mini-Mental State Examination (MMSE). Descriptive analysis and Chi-square test. Results and Discussion: samples are 56 students, the highest gender is men (51%), the range of age 18-21 years old (53.6%), the number of GPA is the same as the one below and above 3 there are 28 (50%). Test Chi Square gender difference with P value of 0.422 GPA gender does not have significant difference to the GPA, based on the age of the results of T-test p-value 0.000, showed age had significant difference to the GPA, where the age is getting younger GPA is getting better, based on the scores of MMSE test, it was obtained p 1.000, MMSE score has no significant difference with the GPA. Conclusion: Gender and MMSE value have no difference with GPA, there is difference between age and GPA, the younger the students the better GPA the students achieve.